Hsa_circ_0001756 drives gastric cancer glycolysis by increasing the expression and stability of PGK1 mRNA - Long Qian; Long Qian; Long Qian; Luman Wang; Hao Chen; Song Wang; Song Wang; Yinfen Hou; Li Xu; Li Xu; Yabin Xia; Yabin Xia; et al. (Frontiers in Immunology)
IntroductionStrategies for preventing high glycolysis in tumour cells are urgently needed. CircRNAs (circRNAs) play important roles in glycolysis. However, the mechanism underlying the effects of hsa_circ_0001756 in gastric cancer (GC) remains unclear.MethodsIn this study, we detected the expression of hsa_circ_0001756 in GC tissues and cells using quantitative real-time polymerase chain reaction (qRT PCR). Construct a silencing and overexpression vector to validate the role of hsa_circ_0001756 in GC. Pulldown and RIP experiments were conducted to verify the identification of miRNA and protein binding to hsa_circ_0001756.ResultsThe expression level of hsa_circ_0001756 in GC tissues and cells is significantly upregulated. The expression level of hsa_circ_0001756 is closely related to TNM stage and tumour size in patients with GC. The proliferation and migration of hsa_circ_0001756-expressing cells in vitro were assessed by functional experiments. Hsa_circ_0001756 was found to not only promote the expression and stability of PGK1 by binding with polypyrimidine tract-binding protein 1 (PTBP1) but also promote glycolysis through the miR-185-3P/PGK1 pathway. We found that the regulatory relationships of competing endogenous RNA (ceRNA) and RNA-binding proteins (RBPs) with hsa_circ_0001756may affect glycolysis in GC.ConclusionThis study provides a theoretical basis for designing drugs that target molecules related to energy metabolism in tumours and provides a new strategy for the clinical treatment of GC.